2008
DOI: 10.1103/physreva.77.012117
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death of entanglement at finite temperature

Abstract: In this paper we consider the decay of quantum entanglement, quantified by the concurrence, of a pair of two-level systems each of which is interacting with a reservoir at finite temperature T. For a broad class of initially entangled states, we demonstrate that the system always becomes disentangled in a finite time i.e. "entanglement sudden death" (ESD) occurs. This class includes all states which previously had been found to have long-lived entanglement in zero temperature reservoirs. Our general result is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 26 publications
5
170
0
Order By: Relevance
“…One of the reasons why X states became so popular in the study of the dynamics of quantum correlations is because of the relatively simple form that the concurrence takes for such states. Moreover since in such studies [41][42][43] they stay in the X form for all times, the simple equation (13) is valid throughout their evolution. To study what types of dynamics preserve the shape of X states we employ the very elegant algebraic characterization of X states presented in [44].…”
Section: Dynamicsmentioning
confidence: 99%
“…One of the reasons why X states became so popular in the study of the dynamics of quantum correlations is because of the relatively simple form that the concurrence takes for such states. Moreover since in such studies [41][42][43] they stay in the X form for all times, the simple equation (13) is valid throughout their evolution. To study what types of dynamics preserve the shape of X states we employ the very elegant algebraic characterization of X states presented in [44].…”
Section: Dynamicsmentioning
confidence: 99%
“…The time evolution of two non-interacting qubits, each of them individually evolving according to (8), is then given by a time dependent density matrix whose elements with respect to the computational basis with 蟻 T i j (t) = 蟻 T * ji (t). That is, the matrix 蟻 T (t) is Hermitian.…”
Section: System Studiedmentioning
confidence: 99%
“…It has been shown that in some cases entanglement can completely disappear in finite times. This phenomenon is known as entanglement sudden death (ESD) [7][8][9][10] and has been observed experimentally by Almeida et al [11]. It is of clear relevance to study and understand ESD and related phenomena occurring during the evolution of open quantum systems, because the actual implementation of quantum computation and other quantum information tasks depend on the longevity of entanglement in multiqubits states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a very general treatment was based on dissipation phenomena in the damped cavity model [11][12][13]. The problem of the influence of the temperature on the induced inter- * e-mail: tomsow@cft.edu.pl actions between qubits via the electromagnetic field and on their entanglement is recently considered in the context of the so-called sudden death of entanglement phenomenon [14][15][16]. Very often this analysis is carried out in the Jaynes-Cummings model [17] in the rotating wave approximation (RWA) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%